Karakteristik Microgreens pada Berbagai Genotipe Jagung (Zea mays L.) - Nurfauziah, Iis Diah; Wijana, Gede; Mayadewi, Ni Nyoman Ari (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024), 2024)
Characteristics of Microgreen in Different Genotypes of Maize ( Zea mays L.) . Microgreen is one of the plant cultivation techniques that can be done in accordance with the concept of urban farming. Plants that are still rarely cultivated as microgreens are corn. Corn microgreens have the main bioactive content, namely carotenoids. Microgreen characteristics of different corn genotypes are not yet known. This study aimed to determine the characteristics of microgreens and determine the superior attributes of corn genotypes cultivated as microgreens. This study used a one-factor completely randomized design (CRD) of 8 levels and 3 replications. The levels used were various corn genotypes i.e. local corn Belok Sidan, local corn Seraya, hybrid corn Pertiwi, hybrid corn Pioneer, sweet corn Bonzana F1, sweet corn Talenta, sticky corn Kumala, and sticky corn Paramita. The results showed that different corn genotypes had different characteristics on the observed variables. Hybrid corn Pertiwi and sticky corn Paramita had superior attributes in the organoleptic test in terms of crispness (3.50; 3.06), flavor (3.47; 2.75), level of liking (2.94; 2.94), and total soluble solids (12.7°brix and 14.3°brix, respectively), local corn Seraya had superior characteristics in carotenoid content (45.42 mg/100g), and local corn Belok Sidan had superior characteristics in fresh weight and dry weight (3.6798 g and 0.4874 g).